2017
DOI: 10.1002/2017gl074866
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Branch Break‐up Systems by a Single Mantle Plume: Insights from Numerical Modeling

Abstract: Thermomechanical modeling of plume‐induced continental break‐up reveals that the initial location of a mantle anomaly relative to a lithosphere inhomogeneity has a major impact on the geometry and timing of a rift‐to‐spreading system. Models with a warmer Moho temperature are more likely to result in “plume‐centered” mode, where the rift and subsequent spreading axis grow directly above the plume. Models with weak far‐field forcing are inclined to develop a “structural‐inherited” mode, with lithosphere deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 57 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…The initial model setup and geotherm were adopted with respect to observation-based models of regional thermal and rheological structure of the continental lithosphere in East Africa (Albaric, D everch ere, Petit, Perrot, & Le Gall, 2009;Artemieva, 2006;Fishwick & Bastow, 2011;P erez-Gussiny e et al, 2009). Rheological parameters were chosen in consideration of extensive and successful experience obtained from heterogeneous continental rifting (e.g., Huismans & Beaumont, 2007;Wenker & Beaumont, 2016 and references therein) and plume-lithosphere interaction modelling (e.g., Beniest, Koptev, & Burov, 2017;Beniest, Koptev, Leroy, Sassi, & Guichet, 2017;Burov, 2011;Burov & Cloetingh, 2010;Burov & Gerya, 2014;Burov & Guillou-Frottier, 2005;Burov, Guillou-Frottier, d'Acremont, Le Pourhiet, & Cloetingh, 2007;Koptev, Cloetingh, Burov, Franc ßois, & Gerya, 2017) including our previous Africa-oriented experiments (Koptev et al, 2015(Koptev et al, , 2016, which have been able to reproduce a number of key features of the central EARS such as timing, surface velocity distribution and large-scale topography [Colour figure can be viewed at wileyonlinelibrary.com] Kelley, 1998;Pik, Marty, & Hilton, 2006). Yet, the southern prolongation of the Western rift by the Malawi rift has not been reproduced in any of these "one-craton" experiments (Koptev et al, 2015(Koptev et al, , 2016.…”
mentioning
confidence: 99%
“…The initial model setup and geotherm were adopted with respect to observation-based models of regional thermal and rheological structure of the continental lithosphere in East Africa (Albaric, D everch ere, Petit, Perrot, & Le Gall, 2009;Artemieva, 2006;Fishwick & Bastow, 2011;P erez-Gussiny e et al, 2009). Rheological parameters were chosen in consideration of extensive and successful experience obtained from heterogeneous continental rifting (e.g., Huismans & Beaumont, 2007;Wenker & Beaumont, 2016 and references therein) and plume-lithosphere interaction modelling (e.g., Beniest, Koptev, & Burov, 2017;Beniest, Koptev, Leroy, Sassi, & Guichet, 2017;Burov, 2011;Burov & Cloetingh, 2010;Burov & Gerya, 2014;Burov & Guillou-Frottier, 2005;Burov, Guillou-Frottier, d'Acremont, Le Pourhiet, & Cloetingh, 2007;Koptev, Cloetingh, Burov, Franc ßois, & Gerya, 2017) including our previous Africa-oriented experiments (Koptev et al, 2015(Koptev et al, , 2016, which have been able to reproduce a number of key features of the central EARS such as timing, surface velocity distribution and large-scale topography [Colour figure can be viewed at wileyonlinelibrary.com] Kelley, 1998;Pik, Marty, & Hilton, 2006). Yet, the southern prolongation of the Western rift by the Malawi rift has not been reproduced in any of these "one-craton" experiments (Koptev et al, 2015(Koptev et al, , 2016.…”
mentioning
confidence: 99%
“…Repeated jumps of midoceanic ridges toward nearby hot spots within oceanic lithosphere have been reproduced numerically by Mittelstaedt et al (2008Mittelstaedt et al ( , 2011 and observed by d' Acremont et al (2010). Mantle upwelling, thus, was confirmed to be one of the key factors in the contrasting continental rifting characterized by both "passive/amagmatic" and "active/magmatic" branches (see also 3-D experiments by Koptev et al, 2015Koptev et al, , 2016Koptev, Cloetingh, et al, 2018) that may further evolve into breakup centers embracing isolated continental block (Beniest, Koptev, Leroy, et al, 2017). Mantle upwelling, thus, was confirmed to be one of the key factors in the contrasting continental rifting characterized by both "passive/amagmatic" and "active/magmatic" branches (see also 3-D experiments by Koptev et al, 2015Koptev et al, , 2016Koptev, Cloetingh, et al, 2018) that may further evolve into breakup centers embracing isolated continental block (Beniest, Koptev, Leroy, et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…In the context of the continental lithosphere, the 2-D thermo-mechanical modeling by Lavecchia et al (2017) showed an abandonment of the rift initially localized in a preexisting zone of lithospheric weakness and associated rift jump toward the thermally activated mantle plume. Mantle upwelling, thus, was confirmed to be one of the key factors in the contrasting continental rifting characterized by both "passive/amagmatic" and "active/magmatic" branches (see also 3-D experiments by Koptev et al, 2015Koptev et al, , 2016Koptev, Cloetingh, et al, 2018) that may further evolve into breakup centers embracing isolated continental block (Beniest, Koptev, Leroy, et al, 2017). In analog models, a complete separation of the microcontinental body from a parent continent is also strongly connected to the thermal weakening due to the presence of a hot spot (Dubinin et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations